A systematic review and meta-analysis assessing the effectiveness of alternative listening devices to conventional hearing aids in adults with hearing loss - Maidment, David W.; Barker, Alexander B.; Xia, Jun; Ferguson, Melanie A. (Taylor & Francis, 2018)
Objective: Recent technological advances have led to a rapid increase in alternative listening devices to conventional hearing aids. The aim was to systematically review the existing evidence to assess the effectiveness of alternative listening devices in adults with mild and moderate hearing loss. Design: A systematic search strategy of the scientific literature was employed, reported in accordance with the Preferred Reporting Items for Systematic reviews and Meta-analyses (PRISMA) checklist. Study sample: Eleven studies met eligibility for inclusion: two studies evaluated personal sound amplification products, and nine studies assessed remote microphone systems (frequency modulation, Bluetooth, wireless). Results: The evidence in this review suggests that alternative listening devices improve behavioural measures of speech intelligibility relative to unaided and/or aided conditions. Evidence for whether alternative listening devices improve self-reported outcomes is inconsistent. The evidence was judged to be of poor to good quality and subject to bias due to limitations in study design. Conclusions: Our overall recommendation is that high-quality evidence (i.e. randomised controlled trials) is required to demonstrate the effectiveness of alternative listening devices. Such evidence is not currently available and is necessary to guide healthcare commissioners and policymakers when considering new service delivery models for adults with hearing loss.